1991
DOI: 10.1007/bf00928679
|View full text |Cite
|
Sign up to set email alerts
|

Role of cytoskeleton and surface lectins inGiardia duodenalis attachment to Caco2 cells

Abstract: An in vitro model of Giardia duodenalis and the Caco2 cell line enable the study of parameters that could play a part in trophozoite attachment. We explored the role of membranous lectins of G. duodenalis in attachment-inhibition studies using carbohydrates in solution. Attachment rates were reduced by 14% and 23% in the presence of 100 mmol/l mannose-6-phosphate and glucose, respectively, as compared with control values. No significant modification was observed after trophozoite trypsinization at room tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 12 publications
0
26
0
Order By: Relevance
“…" Preliminary experiments showed that the preincubation of Caco-2 cells with suspensions of L. johnsonii La1 did not inhibit the complex adhesion of trophozoites to cell monolayers (data not shown). This interaction involves the ventral disk, several contractile elements, and hydrodynamic and mechanical forces, as well as lectin-binding factors (18,21,24,25). The possibility remained that if an antagonistic effect of the bacteria against the parasite existed, it could result from the release of bacterial metabolites or products more than a competitive exclusion or steric hindrance (3).…”
Section: Discussionmentioning
confidence: 99%
“…" Preliminary experiments showed that the preincubation of Caco-2 cells with suspensions of L. johnsonii La1 did not inhibit the complex adhesion of trophozoites to cell monolayers (data not shown). This interaction involves the ventral disk, several contractile elements, and hydrodynamic and mechanical forces, as well as lectin-binding factors (18,21,24,25). The possibility remained that if an antagonistic effect of the bacteria against the parasite existed, it could result from the release of bacterial metabolites or products more than a competitive exclusion or steric hindrance (3).…”
Section: Discussionmentioning
confidence: 99%
“…Using their flagella and ventral disc, trophozoites released in the upper part of the small intestine move to the microvillus-covered surface of the duodenum and jejunum, where they attach themselves (88,116), and play a role in the onset of the pathology (22,34,124). The suction force created by this mode of attachment may damage the microvilli and interfere with the process of food absorption (88,116). Eventually, the rapid multiplication of the trophozoites by binary fission creates a physical barrier between the intestinal epithelial cells and the lumen of the intestine, interfering with the process of absorption of nutrients.…”
Section: Giardiasismentioning
confidence: 99%
“…1A), with normal confluence levels and negligible differences in detachment forces compared to those with plain glass. While it is likely that specific binding is important for parasite-host recognition or interactions in vivo (14), specific binding cannot explain Giardia's robust attachment to treated glass surfaces.…”
mentioning
confidence: 99%